Radioecology monitoring system for mountine areas of the Tisza river basin (Transcarpathia, Ukraine) - Symkanich, O.I.; Svatiuk, N.I.; Maslyuk, V.T.; Glukh, O.S.; Sukharev, S.N.; Sherehiy, A.A. (Problems of Atomic Science and Technology, 2023)
Regularities of distribution, migration and accumulation of natural gamma-active nuclides ⁴⁰K, series of uranium ²³⁸U (²¹⁴Pb, ²¹⁴Bi) and thorium ²³²Th (²¹²Pb, ²¹²Bi, ²²⁸Ac, ²⁰⁸Tl), as well as technogenic ¹³⁷Cs in the bottom sediments of the Tisza region in Transcarpathia (Ukraine) have been established. It is shown that the content of these radionuclides in the bottom sediments is relatively stable along the entire length of the Tisza river and is proportional to the level of its siltation, which largely depends on the morphology of the river. It was found that the total specific activity of natural gamma-active radionuclides (excluding ⁴⁰K) in bottom sediments ranges from 110…139.7 Bq/kg. Areas of accumulation of gamma-active nuclides in the bottom sediments of the studied river have been identified, and the probable causes of this phenomenon have been substantiated. The averaged data of the content of specific activity of radionuclides in the bottom sediments of the Tisza river were used for mapping and forecasting of migration processes, as well as for identification of the studied sections of the river taking into account the geochemical features of the region. Встановлені закономірності розподілу, міграції та акумуляції природних гамма-активних нуклідів ⁴⁰К, рядів урану ²³⁸U (²¹⁴Pb, ²¹⁴Bi) і торію ²³²Th (²¹²Pb, ²¹²Bi, ²²⁸Ac, ²⁰⁸Tl), а також техногенного ¹³⁷Cs у донних відкладах р. Тиси, Закарпатської області. Показано, що вміст цих радіонуклідів у донних відкладах є відносно стабільним за всією протяжністю р. Тиси і пропорційний рівню її замулювання, що в значній мірі залежить від морфології річки. Встановлено, що сумарна питома активність природних гамма-активних радіонуклідів (без урахування ⁴⁰К) у донних відкладах коливається у межах 110…139,7 Бк/кг. Виявлені ділянки акумуляції гамма-активних нуклідів у донних відкладах досліджуваної річки, обґрунтовані ймовірні причини цього явища. Усереднені дані вмісту питомої активності радіонуклідів у донних відкладах р. Тиси використані для картування і прогнозування міграційних процесів, а також для ідентифікації досліджуваних ділянок річки з урахуванням геохімічних особливостей регіону.